Zebrafish BID Exerts an Antibacterial Role by Negatively Regulating p53, but in a Caspase-8-Independent Manner - Qi, Zhitao; Yan, Dong; Cao, Lu; Xu, Yang; Chang, Mingxian (Frontiers in Immunology, 2021)
Bid (BH3-interacting domain death agonist), a member of the Bcl-2 family, plays a crucial role in the initiation of apoptosis. Independent of its apoptotic function, Bid also involves in the regulation of inflammation and innate immunity. However, the role of Bid during bacterial pathogen infection remains unclear. In the present study, Bid of zebrafish (Dario rerio) was cloned and its functions during Edwardsiella ictaluri infection were investigated. Zebrafish Bid enhances the apoptosis rate of Epithelioma papulosum cyprinid (EPC) cells following E. ictaluri infection. Importantly, in vitro and in vivo bacterial invasion assays showed overexpressed Bid could significantly inhibit the invasion and proliferation of E. ictaluri. Realtime qPCR analysis revealed that p53 gene expresssion was downregualted in embryos microinjected with Bid-FLAG. Further, in vitro and in vivo bacterial invasion assays showed that overexpressed p53 increased the invasion and proliferation of E. ictaluri. Moreover, the invasion and proliferation of E. ictaluri were inhibited when co-overexpressed Bid and p53 in vivo and in vitro. Further, the numbers of E. ictaluri in larvae treated with Z-IETD-FMK (caspase-8 inhibitor) were higher than that of larvae without Z-IETD-FMK treatment. Whist, the number of E. ictaluri in larvae microinjected with bid-Flag decreased significantly, even if the larvae were treated in advance with Z-IETD-FMK. Collectively, our study demonstrated a novel antibacterial activity of fish Bid, providing evidence for understanding the function of apoptosis associated gene in pathogen infection.